LEGAL RISKS IN SALE TRANSACTIONS OF SHARES OF A LIMITED LIABILITY COMPANY CONDUCTED OUTSIDE THE TERRITORY OF THE REPUBLIC OF POLAND - Tomasz Jabłoński (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
Sale transactions of shares of a limited liability company may involve numerous risks, the negative effects of which the transaction parties are exposed to. In this paper only those risks have been discussed, which may occur in case of transactions conducted outside the territory of the Republic of Poland. Those risks are connected to the law applicable to the said transaction, a form of legal action subject to the law applicable to the said transaction, and depending on the particular transaction – also the acquisition of a share covered with a non-cash contribution in the share capital and the recognition of the said shares as foreign securities. Although there is no possibility of a precise measurement and evaluation of the probability of negative effects concerning risks related to the use of percentage rates or similar, they may be classified as risks: low, medium and high. The aim of this paper is to submit the classified risks to the future parties of such transactions, which may occur when conducting the title legal action, and their possible, negative consequences, so that the parties may exercise due diligence.